Sequence Stratigraphy and Sedimentary Environment of the Shiranish Formation, Duhok region, Northern Iraq - Alsultan, Hamid A. A.; Hussein, Mohammed L.; Al-Owaidi, Mohanad R. A.; Al-Khafaji, Amer J.; Menshed, Mahdi A. (Iraqi Journal of Science, 2022)
The Shiranish Formation is cropped out in several areas in northern Iraq. A stratigraphic and facies study was conducted within the Duhok region to determine the sedimentary environment. Three microfacies, reflecting the various subenvironments within different shelf parts of the deep sea, have been identified within the Shiranish Formation. Four depositional environments are identified: slope, the toe of slope, deep shelf, and deep-sea or cratonic deep basin. The Shiranish Formation in the Duhok region, Northern Iraq, was deposited in an open shelf carbonate platform. The Shiranish Formation sequence is divided into six third-order cycles in the study area. These asymmetrical cycles reflect an imbalance between the relative level of the sea and the production of carbonate, and each one reflects a rise in the sea level following a period of standstill. There is a two-sequence boundary type SB-2 that defines the surface. The Shiranish sequence developed in a high-subsidence area that played the main role in the evolution of the formation. It was deposited on a carbonate platform with high subsidence due to major transgression, wherever the successive sea-level rise and stillstand episodes persist.